Drug Dependence and Addiction, III. - Volkow, Nora (American Journal of Psychiatry, 2004)
A study was conducted to examine the neural basis for the effect that drug abusers' subjective responses to a drug are more pleasurable when the person expects to receive the drug than when they do not. The response of brain glucose utilization to intravenous methylphenidate in cocaine abusers under distinct conditions of expectation and no expectation was investigated. Findings revealed that the reinforcing effects of drugs were not merely a function of their pharmacological effects but also of the expectations of their actions.